Sir Emery Walker correspondence - Walker, Emery, Sir, 1851-1933.
Letter written by Walker to William Dana Orcutt relating to Walker's association with T. J. Cobden-Sanderson and William Morris in the revival of fine printing.
Handwritten transcript.
British printer and engraver.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Cobden-Sanderson, T. J. -- 1840-1922.; Morris, William, -- 1834-1896.; Orcutt, William Dana, -- 1870-1953 -- Correspondence; Fine books -- Great Britain; Engravers; Printers